PENGARUH PERKEMBANGAN TEKNOLOGI, KUALITAS SDM, PERTUMBUHAN EKONOMI, DAN INVESTASI TERHADAP TPT - Firdausi, Ismy Angeia (Journal of Development Economic and Social Studies, 2024)
Unemployment is a macro problem that grows due to the imbalance between economic growth and increased employment. East Java Province made various efforts to reduce the open unemployment rate. To overcome the unemployment problem in East Java, several indicators are of concern to be studied, namely technological development, quality of human resources (HR), economic growth, and investment in 2015-2022. The purpose of this study is to findout the factors that can affect TPT in East Java.  This study uses panel data, through classical assumption tests to hypothesis tests, with secondary data types coming from the official website of BPS (Central Statistics Agency). The estimation results suggest that technological developments, the quality of human resources, and investment tend to increase the number of TPT in East Java. Meanwhile, economic growth tends to reduce the TPT figure in East Java. This research can be a learning material about unemployment.